Does the major aluminium-resistance gene in wheat, TaALMT1, also confer tolerance to alkaline soils? - Silva, Carolina M. S. [UNESP]; Zhang, Chunyan; Habermann, Gustavo [UNESP]; Delhaize, Emmanuel; Ryan, Peter R. (Springer Nature, 2018)
Aim: A major limitation to plant growth in acid soils is the prevalence of toxic Al3+. Most genotypic variation for acid soil-tolerance in wheat is linked with the Al3+-activated efflux of malate anions from roots which is controlled by TaALMT1 on chromosome 4DL. Recent studies have also linked TaALMT1 with tolerance to high pH solutions and alkaline soils. This study tested the hypothesis that an Al3+-resistant allele of TaALMT1 also confers tolerance to alkaline conditions. Methods: The near-isogenic wheat lines, ET8 (Al3+-resistant) and ES8 (Al3+-sensitive), have different alleles of the TaALMT1 gene and contrasting resistance to Al3+ toxicity. Growth of these lines was compared in acid and alkaline soils with contrasting mineralogy and in a range of high pH hydroponic solutions of varying composition. Results: No consistent differences in root or shoot growth were detected between the lines in the alkaline soils or in the high pH hydroponic treatments. Malate efflux was detected from ET8 in acidic solution with Al3+ but no substantial malate efflux was detected at pH 9.0 treatment with added Na2SO4. Conclusion: The results are inconsistent with the hypothesis that the TaALMT1 gene confers an advantage to wheat on alkaline soils.
Keywords: Acidic; Alkaline; Aluminum; Boron; Malate; Resistance; Soil; TaALMT1; Tolerance; Wheat